Thermodynamics, geometrical frustration and quantum fluctuations in coupled spin chains - Sznajd, J. (Condensed Matter Physics, 2009)
The linear-perturbation real space renormalization transformation (LPRG) is presented and applied to the
study of quantum spin chains coupled by interchain interaction (k₁) weaker than intrachain one (k). The
method is examined in two exact solvable cases: Ising chains on the square and triangular lattices and quantum
XY chain. For the Ising model, in the second order in the cumulant epansion, the deviation of the critical
temperature from the exact value is less than 1% for 0.5k > k₁ > 0.15k, but even in the case of the standard
Ising model (k₁ = k) we found the value of Tc which differs by 2% from the exact one. For the quantum XY
chain the deviation of the free energy value found by using LPRG from the exact Katsura result is less than
1% for T/J > 1, and for rather low temperature T/J = 0.08 is about 6%. The LPRG is used to study the
effects of interchain frustration on the phase transition in 2D Heisenberg spin chains with easy axis along the
z direction. It is shown that contrary to the pure Ising model in systems with in-plane interactions (XY), the
interchain frustration does not destroy the finite-temperature transition. However, such a frustration changes
the character of the phase transition from Ising-like to, probably, Kosterlitz-Thouless-like. We have also applied
the LPRG method to the calculation of the isothermal magnetocaloric coef cient (Mт) for several spin
models in disordered phases. Is is demonstrated that in the presence of antiferromagnetic fluctuations, Mт
changes sign at some value of the magnetic field. Generally, Mт is negative if magnetic field competes with
a short-range order, and consequently it can be an indicator of the change in the short-range correlation. Сформульовано лiнiйно-пертурбативне ренормалiзацiйне перетворення у дiйсному просторi (ЛПРП), що використовується для вивчення квантових спiнових ланцюжкiв, зв’язаних мiжланцюжковою взаємодiєю (k₁), яка є слабшою за взаємодiю (k) мiж спiнами у ланцюжку. Метод протестовано для двох точно розв’язуваних моделей: Iзингiвських ланцюжкiв на квадратнiй та трикутнiй ґратках i квантових XY ланцюжкiв. Для моделi Iзинга у другому порядку кумулянтного розкладу показано, що вiдхилення критичної температури вiд точного значення є меншим 1% для 0.5k > k₁ > 0.15k; однак навiть у випадку стандартної моделi Iзинга (k₁ = k) отримано значення Tc, що вiдрiзняється вiд точного на 2%. Для квантового XY ланцюжка вiдхилення вiльної енергiї, що знайдена методом ЛПРП, вiд точного результату Кацура не перевищує 1% для T/J > 1, а для доволi низької температури T/J = 0.08 складає бiля 6%. Метод ЛПРП використовується для вивчення впливу мiжланцюжкової фрустрацiї на фазовий перехiд у двовимiрних Гайзенбергiвських спiнових ланцюжках з вiссю легкого намагнiчення вздовж напрямку z. Показано, що на вiдмiну вiд чисто Iзингiвської моделi, у системах iз планарною XY взаємодiєю мiжланцюжкова фрустрацiя не порушує фазовий перехiд при скiнчених температурах. Однак, така фрустрацiя змiнює характер фазових переходiв вiд iзингiвського типу до, iмовiрно, переходiв типу Костерлiца-Таулса. Ми використали також метод ЛПРП для розрахунку iзотермiчного магнетокалоричного коефiцiєнта (Mт) кiлькох спiнових моделей у невпорядкованих фазах. Показано, що за наявностi антиферомагнiтних флуктуацiй,Mт змiнює свiй знак при певному значеннi магнiтного поля. Загалом Mт – вiд’ємна величина, якщо магнiтне поле конкурує з близьким порядком, i тому це може служити iндикатором змiни короткосяжних кореляцiй.